A Subtitling Analysis Of Noun Phrase In The Magic Of Belle Isle Movie - Stianingrum, Winda; , Dr. Dwi Haryanti, M. Hum; , Mauly Halwat Hikmat, Ph.D (2015)
The research paperanalyzes noun phrase in subtitling The Magic of Belle Isle movie. The study aims (1) to identify subtitling variations of noun phrase found in The Magic of Belle Isle movie and (2) to describe the readability subtitling of noun phrase found in The Magic of Belle Isle movie. The type of this research is descriptive qualitative research. The object of the study is the movie entitled The Magic of Belle Isle and its subtitling. The data of this study is clauses and sentences consisting noun phrase found in The Magic of Belle Isle movie. Data source used in this research are the documentation of the data research paper and the informants or three raters. The researcher uses document, questionnaire, and interview three raters in collecting data. The data are analyzed by using comparing method. Based on the analysis, there are 6 types of English noun phrase. 514 data or 75.8% of the data are covered by noun phrase type 1 translated into 15 variations in Indonesian noun phrase.NP1 subtitling variation has 514 data or 75.8%, NP2 subtitling variation has 134 data or 19.5%, NP3 subtitling variation has 5 data or 0.9%, NP4 subtitling variation has 4 data or 0.8%, NP7 subtitling variation has 10 data or 1.8%, then NP8 subtitling variation has 7 data or 1.2%. So, it finds 674 data or 100% in subtitling variation. In their readability, NP1 subtitling variation has score 2.9, NP2 subtitling variation has score 2.9, NP3 subtitling variation has score 3, NP4 subtitling variation has score 2.9, NP7 subtitling variation has score 2.8, and NP8 subtitling variationhas score 3.Based on the average of the three raters 623 data or 92.4% belongs to high readability with parameter 2.7 - 3.In the parameter 2 - 2.6 finds 46 data or 6.8% is medium readability. Then, 5 data or 0.8% in parameter < 2 belongs to low readability. It can be concluded that 99.7% data noun phrase subtitling variations are readable.